Who said what: Subject positions, rhetorical strategies and good faith - Anton, Corey; Peterson, Valerie V. (Communication studies, 2003)
The first part of this paper briefly sketches out the idea of subject position by advancing two general types of subject position, showing how they differ and overlap. The second part discusses subject position as it is employed in argumentation, and specifically how it is used as a rhetorical trope to claim or disclaim legitimacy. The third part offers the concept of "good faith"; to address how future research/theory along these lines may provide useful contributions to rhetorical theory and practice.